Vicarious Liability in Personal Data Protection: Vicarious Liability dalam Perlindungan Data Pribadi - Claudia, Zulian; Gunadi, Ariawan (Rechtsidee, 2023)
This study explores the legal responsibility and ideal concepts in compensating victims of personal data misuse, focusing on the ambiguous regulations within Indonesia's Personal Data Protection Act (UU PDP). The research, conducted through a normative-juridical approach employing conceptual and legislative methods, assessed primary legal materials including UUD NRI 1945 and UU PDP, along with secondary legal materials like books, journals, and non-legal materials such as language dictionaries. The results identified an existing lack of clarity in the UU PDP regarding the embraced accountability concept, potentially impairing the optimal filing of compensation claims by personal data subjects. It concluded that adopting the legal accountability concept of vicarious liability could ensure legal certainty for victims and simplify obtaining compensation for personal data misuse. The study implies the necessity for the adoption of vicarious liability, particularly in compensating victims of data misuse, by future institutions involved in personal data protection. Highlights: Ambiguity in Regulation: The UU PDP's lack of clarity concerning legal accountability may lead to suboptimal compensation claims for personal data subjects. Ideal Concept Identified: The vicarious liability concept was determined as an ideal basis for legal accountability in compensating victims of personal data misuse. Implication for Future Institutions: The findings suggest the importance of adopting vicarious liability in future data protection institutions, particularly regarding compensation for data misuse victims. Keywords: Vicarious Liability, Personal Data Protection, Legal Responsibility, Compensation, Normative-Juridical Analysis